(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Food security exists when all people, at all times, have access to sufficient, safe and nutritious food to maintain healthy and productive lives. This study was carried out to investigate the household food security status of dairy farmer at three villages of Shahjadpur Upazila of Sirajganj District. This study was based on primary data and a semi-structured interview schedule was used for collecting data during January to March 2018. Data were collected from a random sample of 60 where the total dairy farmers were 240. Food security status of household of dairy farmer was measured on the basis of their per capita calorie consumption per day. Pearson’s Product Moment Coefficient Correlation (r) was computed to explore the relationship of the respondents selected characteristics and their food security status. It is 40% percent moderately food secured per year, 25% household had food secured per year and 35% households were low food secured per year. Dairy farmer’s Annual income, training, experience, credit received had a significant positive relationship with their household food security status. The Findings of the study would be helpful for policy makers. Government and non-government organizations work for development of tribal people; this study may help them achieve their goal. It will be helpful for the government to ensure their food security in the sense that they may be aware of the food insecure situation if the findings of the study are revealed to them Res. Agric., Livest. Fish.6(3): 379-387, December 2019